A techno-economic review of biomass gasification for production of chemicals. Issue 8 (3rd August 2018) - Wang, Shu-Wen; Li, De-Xun; Ruan, Wen-Biao; Jin, Chen-Lin; Farahani, Mohammad Reza
ABSTRACT: Gasification is a thermochemical process which can be used as a low-emission and highly efficient method to produce syngas and chemicals such as biomethanol and dimethyl ether (DME). In this paper, a review of technologies and methods for economic production of chemicals through gasification of biomass and other fuels has been carried out. A variety of techno-economic studies and analysis have been proposed in order to better understand the technical and economic assessments during the biomass gasification. Results showed that the methanol production cost for biomass (wood) is from 195 to 935 €/t, for waste residues is from 200 to 930 €/t, for coal is from 160 to 480 €/t, and for natural gas is from 90 to 290 €/t. It also concluded that fuel (wood) cost has positive linear relationship with ethanol production cost, meaning as the feedstock cost increases from 30 to 50 /day-ton, the ethanol production cost enhances from 1.66 to 1.95 /gal.